Sampling for Integrated Audit Objectives-A Comment. - Blocher, Edward (The Accounting Review, 1978)
Abstract The article is based upon the apparent reasonableness of solutions of the Ijiri-Kaplan (I-K) model for a set of data obtained from a financial institution and a Tuscon office supply company. To demonstrate the usefulness and validity of a model should, in fact, require some evidence that the use of the model will, in some way, generally improve audit decision making. In order to assess the potential for the model to improve audit decision making, certain important issues regarding audit sampling objectives and related measurement problems need to be clarified. First, there is a problem in how an error is defined for the model. For example, the I-K model is defined only for errors which have a dollar impact on an account balance. Further, the I-K model makes no allowance for qualitative differences among different errors. For example, one single extension error, say, in preparing an invoice would be of much less significance for the auditor than would be a single extension error in pricing inventory which might signal multiple errors of the same type.